Exploring secondary students’ reflective thinking skills in statistics based on mathematical ability - Masduki Masduki; Mutiara Hisda Mahmudah; Windi Hastuti (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2026)
Reflective thinking plays a vital role in mathematics learning, particularly in solving complex problems. Understanding students’ reflective thinking abilities across its aspects—technique, monitoring, insight, and conceptualization—is essential for selecting appropriate instructional methods. This study aims to describe junior high school students’ reflective thinking abilities in learning statistics based on their initial mathematical ability. A qualitative approach with a case study design was used to explore reflective thinking skills in the four aspects: technique, monitoring, insight, and conceptualization. The research participants consisted of 30 seventh-grade students from a junior high school in Boyolali, Indonesia, who were grouped into three categories based on their mathematical ability: high, medium, and low. Data were collected through reflective thinking tests, observations, and interviews, and analyzed using the constant comparative analysis method. The results reveal a hierarchical relationship between mathematical ability and reflective thinking. Students with high mathematical ability demonstrated complete reflective thinking, fulfilling all indicators across the four aspects. Students with moderate ability exhibited partial reflective thinking, meeting some indicators but not fully optimizing others. Students with low mathematical ability showed the weakest reflective thinking skills, meeting indicators only partially in technique, monitoring, and insight, while failing to achieve the conceptualization indicators optimally. These findings confirm that foundational mathematical knowledge is a critical determinant of students’ capacity for deep reflective problem solving in statistics and provide important implications for the development of targeted instructional methods.